2022
DOI: 10.18502/kls.v7i3.11110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seaweed Combined With an Endophytic Microbial Consortium on Two Varieties of Chili

Abstract: In Indonesia, the chili (Capsicum annuum L.) is popular. Unfortunately, its current productivity is lower than its potential yield. The low productivity is due to the cultivation methods or varieties used in the field. Seaweed is a known bio-stimulant and combining it with a microbial consortium could be an effective way to boost crop productivity. The goal of this study was to examine how a combination of bio stimulants enriched with a microbial consortium can affect the productivity of two chili varieties, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
1
3
0
1
Order By: Relevance
“…Our results found that bio-stimulant with pre-dried treatment (Bio A) has a better effect on promoting antibacterial properties in the seedling stage than Bio B, while Bio B treatment presented a better performance in speed of seed germination and germination percentage parameters than Bio A. This result is similar to [48] where the application of bio-stimulants on shallot plants can reduce the chemical fertilizer by 25%, while the result is same as 100% of chemical fertilizer application. Nevertheless, the seedling growth parameters in both bio-stimulants in all concentrations and soaking times, were not better than control.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Our results found that bio-stimulant with pre-dried treatment (Bio A) has a better effect on promoting antibacterial properties in the seedling stage than Bio B, while Bio B treatment presented a better performance in speed of seed germination and germination percentage parameters than Bio A. This result is similar to [48] where the application of bio-stimulants on shallot plants can reduce the chemical fertilizer by 25%, while the result is same as 100% of chemical fertilizer application. Nevertheless, the seedling growth parameters in both bio-stimulants in all concentrations and soaking times, were not better than control.…”
Section: Resultssupporting
confidence: 73%
“…Production of bio-stimulants began with preparing Ulva seaweed and the selected endophytic bacteria from shallot plants that have been identified molecularly in previous research [46]. This bio-stimulants formula, which are a consortium of endophytic bacteria with the addition of seaweed extract, was made into 2 formulas, namely formula A (Bio-stimulant A) with seaweed preparation using oven technique (pre-dried treatment at 60 0 C for 72 hours), and formula B (Bio-stimulant B) with seaweed preparation without oven technique.…”
Section: Bio-stimulants Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sebagian petani di Indonesia sudah mulai mengenal, mempelajari dan menggunakan TSS di lapangan (Mardiyanto et al, 2017;Roessali et al, 2019;Sayaka et al, 2020). Penelitian terkait penambahan biostimulan pada benih atau bibit TSS sebelum ditanam telah dilakukan dengan menggunakan air kelapa (Andayani, 2020), hormon (Hasanah et al, 2021;Rantau et al, 2021;Wahyuni et al, 2021), PGPR (Sudaryono, 2018), dan mikroba (Azmi et al, 2022;Haring et al, 2019). Di lain sisi, petani bawang merah sering menggunakan Previcur-N untuk merendam benih TSS sebelum semai.…”
Section: Pendahuluanunclassified